The importance of cranium bones fractures proving at expert rating of brain injury severity - Shamaev, M. I.; Semisalov, S. Ya.; Semenov, A. V. (Ukrainian Neurosurgical Journal, 2005)
The importance of cranium bones fractures is determined in medicolegal examination (МLE), using the special information system "Expert — CCT", into which database of 27 206 supervision (f.074/o) with cranio-cerebral trauma (CCT) were entered. The CCT treatment outcomes depend on cranium bones fractures, investigated on 2697 case reports (f.033/o). There was a cranium fracture in 1084 (40,2%) cases. The mortality at CCT with the isolated fornix or cranium basis fracture authentically did not differ from number of fatal outcomes at brain bruises in average and heavy degree without cranium fracture. The combination of fornix and cranium basis bones fractures caused to mortality outcomes in most cases and more often, than isolated fractures, that could serve as authentic acknowledgement for MLE of CCT severity with attributes, danger for life. The isolated fornix or cranium basis bones fracture did not influence on a trauma outcome and in studied cases the degree of CCT severity at MLE realization should be estimated on character and severity of traumatic brain substance injuries. These offers should be taken into account, while developing new edition of the Ministry of public health of Ukraine Order on improving MLE of a CCT.